PENGARUH BUDAYA ORGANISASI, KOMPETENSI PEGAWAI DAN AKUNTABILITAS KINERJA TERHADAP KINERJA SKPD DI KABUPATEN TABALONG - Agus Sugiarto (JURNAL KINDAI, 2020)
This study aims to determine : (1) The influence of organizational culture on SKPD performance, (2) Effect of employee competence on the performance of SKPD,(3) The effect of performance accountability on SKPD performance, (4) The influence of organizational culture, employee competence and performance accountability simultaneously influences the performance of the SKPD , (5) The influence of organizational culture, employee competence and performance accountability simultaneously influences the performance of the SKPD. This research is a descriptive study with a quantitative approach. Quantitative data collection was carried out using a survey method by using questionnaire instruments. The research locations were in Tabalong Regency on 9 SKPDs that had been evaluated by SAKIP. Results of the study show that : (1) An organizational culture, employee competence and accountability for performance has a positive and significant impact on the performance of SKPD scope of sectors in the Government of Tabalong, (2) Competence of employees having the most dominant influence on the performance of SKPD compared with the influence of organizational culture and performance accountability in the District Government of Tabalong. Keywords : Organizational Culture, Competence, Accountability, Performance.